2017
DOI: 10.1177/0272684x17740694
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Payer–Community Partnerships: The EmblemHealth Neighborhood Care Program

Abstract: Comprehensive and innovative strategies are needed to address and manage chronic diseases and conditions and to reduce health disparities. EmblemHealth Neighborhood Care (EHNC) sites provide community-based linkages across payers, health providers, and delivery systems and underserved communities using culturally sensitive methods tailored to meet the needs of the community. This article describes this novel initiative and early indicators of its feasibility. Three EHNC sites were established in New York City:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Five studies enrolled children and adults (n = 2633), 3 studies enrolled participants of all ages (n = 1280), and 1 study enrolled children/adolescents and older adults (n not reported). Fifty-four studies (n = 120 245) recruited a general, nontargeted patient population; all other studies (n = 5 858 351) targeted patients with particular demographic, medical, or social risk characteristics. Participants were most frequently selected based on specific social risk(s) (eg, homeless, low income) (22 studies, n = 25837) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies enrolled children and adults (n = 2633), 3 studies enrolled participants of all ages (n = 1280), and 1 study enrolled children/adolescents and older adults (n not reported). Fifty-four studies (n = 120 245) recruited a general, nontargeted patient population; all other studies (n = 5 858 351) targeted patients with particular demographic, medical, or social risk characteristics. Participants were most frequently selected based on specific social risk(s) (eg, homeless, low income) (22 studies, n = 25837) …”
Section: Resultsmentioning
confidence: 99%
“…Fifty-two studies provided data on patient- or clinician-reported satisfaction or challenges after implementation of social risk screening or interventions (eTable 4 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations